19. PLEKHA5 REGULATES TUMOR GROWTH IN METASTATIC MELANOMA. (4th August 2020) - Oria, Victor; Zhang, Hongyi; Zhu, Huifang; Deng, Gang; Zito, Christopher; Rane, Chetan; Zhang, Shenqi; Weiss, Sarah; Tran, Thuy; Adeniran, Adebowale; Zhang, Fanfan; Zhou, Jiangbing; et al.
Abstract: Understanding the mechanisms behind melanoma brain metastasis, a disease that continues to portend a poor prognosis, will lead to the identification and development of novel drug targets. We previously identified PLEKHA5, a gene involved in brain development, as a novel molecule implicated in melanoma brain metastasis. Our aim was to further characterize the function of this protein in brain-tropic melanoma. We established stable loss- and gain-of-function cell lines to explore the underlying mechanisms of PLEKHA5-mediated tumor growth. The effect of PLEKHA5 expression silencing on proliferation and tumor growth was assessed using both in vitro systems and xenograft models of brain-tropic melanomas, respectively. The clinical relevance of PLEKHA5 dysregulation in brain metastasis was also investigated in two unique cohorts of melanoma patients with cerebrotropic disease and included analysis of matched cranial and extra-cranial specimens. Knock-down of PLEKHA5 in brain-tropic melanoma cells negatively regulated cell proliferation by inhibiting G1 to S cell cycle transition. This coincided with up-regulation of PDCD4, p21, and p27, as well as the downregulation of pRb protein, involved in the regulation of cell cycle. Conversely, the ectopic re-expression of PLEKHA5 had an inverse effect. Subcutaneous and direct cranial injections of PLEKHA5 knock-down cells in nude mice significantly inhibited tumor growth, while its overexpression upregulated the growth of tumors. This reduction in tumor growth in vivo might be attributed to decreased phosphorylation of Akt (S473) and mTOR (S2448), key mediators for tumor growth and survival. Our results demonstrate the role of PLEKHA5 as a mediator of melanoma brain metastasis. Our findings highlight the significance of PLEKHA5 as a possible regulator of cell cycle transition via crosstalk with the ubiquitin-proteasome and PI3K/AKT/mTOR signaling pathways, driving the proliferation and growth of brain-tropic melanomas. Our studies suggest that PLEKHA5 targeting should be further investigated for melanoma brain metastasis patient population.